Jual Beli Uang Kuno Perspektif Ulama NU (Nahdlatul Ulama) Dan Ulama PERSIS (Persatuan Islam) Garut - Sulthonuddin, Bung Hijaj; Ali, Bintang Sri (STAI Al Musaddadiyah Garut, 2023)
Buying and selling is an exchange economic transaction activity in order to meet daily needs. Such as ancient money buying and selling transactions that are in great demand by the people of Toblong Village. Ancient rupiah money can be valued at a price higher than the nominal that is erased on the ancient money. As for the formulation: (1) How is the practice of buying and selling ancient money transactions in Toblong Village? (2) What is the view of 'Ulama NU (Nahdatul 'Ulama) and 'Ulama Persis (Islamic Union) Garut on the transaction of buying and selling ancient money? The objectives are: (1) To find out the practice of buying and selling ancient money transactions in Toblong Village (2) To find out the views of 'Ulama NU (Nahdhatul 'Ulama) and 'Ulama Persis (Islamic Union) Garut on ancient money buying The results of this study are in the perspective of 'Ulama NU (Nahdlatul 'Ulama) and 'Ulama Persis (Islamic Union) Garut, it is known that the transaction of buying and selling ancient money in Toblong Village is in accordance with the pillars and conditions of buying and selling, so the sale and purchase of ancient money is legal as long as between the two parties are mutually pleasing, because ancient money is an object or item that has artistic value and historical value. In addition, what is traded is not about the nominal, but the historical value and artistic value contained in the ancient money.and selling transactions in Toblong Village. This type of research is field research using a qualitative approach.